Measurement of Spiritual Care Competence: A Literature Review - Wahyu Kurniasih; Dodi Wijaya; Anisah Ardiana (Indonesian Journal of Global Health Research, 2025)
The measurement of spiritual care competence is a crucial aspect of healthcare, particularly in nursing and mental health settings, where holistic care is emphasized to achieve well-being for patients, especially those with terminal conditions. However, determining the appropriate instrument to measure spiritual care competence in nurses is not an easy task. This study aims to identify the most suitable instruments for measuring spiritual care competence in nurses in Indonesia. The method used in this study is a literature review. The keywords used to search for relevant journals are "Nurse" AND "Competence" AND "Spiritual Care." The researcher utilized the Scopus, ScienceDirect, PubMed, and ProQuest databases. The journals included in the review are limited to those published in the last five years over the period from 2020 to 2024 and written in English. Initially, 2,301 journal articles were identified; following a screening and elimination process, 12 articles were selected as suitable for inclusion in this research. This study identified 2,301 journals, which were subsequently filtered for duplicates, irrelevant content, and interventions, resulting in 12 relevant journals. The review found that the instruments used to measure nurses' competence in spiritual care included the Spiritual Care Competence Scale (SCCS), the Spirituality and Spiritual Care Assessment Scale (SSCAS), the Spiritual Care Rating Scale (SSCRS), and the Spiritual Care-Giving Scale (SCGS). This review indicates that the variation in the use of instruments to measure nurses' competence in providing spiritual care is due to differences in respondent characteristics, as well as variations in beliefs and cultures.